Between Mosque and Market: the Muslim Community in Quiapo, Metro Manila - Kuntowijoyo Kuntowijoyo (Studia Islamika, 1994)
The Muslim community is a minority part of the entire Filipino nation. Census 1975 showed that their population is only about 5 percent of the entire population of this country. Most Muslim communities lived in Southern provinces: the islands of Mindanao, Sulu, Basilan, Palawan, Balabac, Tawi-tawi and so on. Linguistically and ethnically, they are composed of Maguindanao, Marano, Iranos, Sangir, Kalagon, and Samal. History shows that the Muslim community is always involved in the struggle against foreign powers, such as Spain, the United States, Japan, and other tribes in the Philippines alone. To form the Philippines, even now, they continue to engage in the struggle to free themselves.DOI: 10.15408/sdi.v1i3.849